Les chiffres macabres de la létalité policière.L’évaluation juridique des “Actes de résistance” à Rio de Janeiro - Michel Misse; Carolina Christoph Grillo; Natasha Elbas Néri (Sociétés et Jeunesses en Difficulté, 2015)
This article presents the main results of the research entitled "Acts of Resistance: an analysis of the homicides carried out by the police in the city of Rio de Janeiro", between the years 2009 and 2011. The main purpose of the research was to follow a sample of the judicial treatment of cases of murder committed by the police which were initially registered as "homicide resulting from Acts of Resistance", in other words with the presumption of legitimate defence. We sought to analyse the penal process for these cases and to understand how the classifications and official accounts of the deaths so categorized are produced. We analysed how they were investigated by the police and pursued by the prosecution. The aim was to identify the factors which influence the course of the investigations and the practices involved in the construction of the events in order to legitimize or to challenge the legality of the police action.